Modelling session types using contracts - HENNESSY, MATTHEW; BERNARDI, GIOVANNI (My University, 2011)
Session types and contracts are two formalisms used to study client- server protocols. In this paper we study the relationship between them. The main result is the existence of a fully abstract model of session types; this model is based on a natural interpretation of these types into a subset of contracts.
PUBLISHED
Keywords: Computer Science; client- server protocols